Hydropower Development in Nepal: Status, Opportunities and Challenges - Bhatt, Pawan; Joshi, Khem Raj (Journal of UTEC Engineering Management, 2024)
DOI: https://doi.org/10.36344/utecem.2024.v02i01.011Nepal is endowed with huge water resources. The available water resources and altitudinal topography provide the ideal situation for the generation of hydropower. Nepal, since about the century ago had started to generate hydro energy but its development over the time is not satisfactory and importing fossil-based fuel significantly. Based on secondary materials, this paper tries to analyses the status of self-reliant energy generation reviewing its development trend within the country. It outlines the   current status of hydropower generation, opportunity associated with it and major challenges therein. Paper argues that though Nepal has developed only 3 % of hydro energy so far, it has    been approaching toward    saturation of its national demand very soon. Replacement of imported fossil fuel by its self-reliant hydro energy is very urgent action to be adopted but it’s quite challenging. The socio-economic transformation of country by utilizing its own generated energy is the most effective way to gear toward the path of prosperity. Acknowledging its major development challenges, formulation of investment friendly policy, power connectivity with reginal economy could drive the nation toward the sustainable development through utilization of naturally endowed water resources.